Taking the train – and the strain - Mohd Mahudin, Nor Diana (2013)
Previous studies on train overcrowding are limited to examining direct effects of passenger density rather than spillover effects. The purpose of this study is to investigate the possible effects of crowding on passengers’ experience of stress and how such effects might spill-over to their overall well-being. Quantitative data gathered via a cross-sectional field survey of 525 peak time commuters were analysed using structural equation modelling. The results indicate that passengers perceived crowding in terms of three components:(1) evaluation of the psychosocial aspects of the crowded situation, (2) evaluation of the ambient environment, and (3) affective reactions to the crowded situation. These components together with passenger density can positively predict the experience of stress, which can then spill over to the work and personal lives of commuters.